Avaliação e Controlo de Treino Intervenção na prevenção de lesões numa equipa Profissional de Futebol - Mário Filipe Cardoso Ribeiro (2018)
The process of doing an internship involves working on planning, intervention and reflecting upon the experiences lived during it. Concerning these experiences, this report aims to present the work made by the intern about his training's intervention, such as in evaluating and controlling the practice itself, maximizing the athlete's performance and preventing injuries. This internship's report was made during the 2nd cycle in High Performance Training in FADEUP, in a professional football team - CD Feirense - during a whole season. A revision through specific literature was made to create a theorical and scientific base, analyzing the processes of organizing and managing the training during a whole season in the intervention areas mentioned above. Having this theorical support and the standard morphocyle of the season, the implemented dynamics were presented in the four dimensions that structure microcyle, ending with a critical reflection to the work. Through the experience given by the internship, along with the scientific evidence collected in literature sources, it is possible to conclude that: (1) It is fundamental to define the evaluation instruments, the control to introduce in the team and uniform its collecting procedure; (2) The inclusion of the evaluation instruments and the control of the athlete's effort, whether they are for objective evaluation (GPS), or for more subjective (RPE), may have a fundamental contribution in managing charges, controlling the training and preventing injuries; (3) the data obtained using these tools must have a more determinant role in managing and in the prescription of a training's charges.